Platycodin D Inhibits Inflammatory Response in LPS-Stimulated Primary Rat Microglia Cells through Activating LXRα–ABCA1 Signaling Pathway - Fu, Yunhe; Xin, Zhuoyuan; Liu, Bin; Wang, Jiaxin; Wang, Jingjing; Zhang, Xu; Wang, Yanan; Li, Fan (Frontiers in Immunology, 2018)
Platycodin D (PLD), an effective triterpene saponin extracted from the root of Platycodon grandiflorum, has been reported to have anti-inflammatory effect. The aim of this study was to investigate the anti-inflammatory effects of PLD on LPS-induced inflammation in primary rat microglia cells. The production of TNF-α, IL-6, and IL-1β were detected by ELISA. The expression of LXRα, ABCA1, TLR4, and NF-κB were detected by western blotting.The results showed that PLD significantly inhibited LPS-induced ROS, TNF-α, IL-6, and IL-1β production in BV2 microglia and primary rat microglia cells. PLD also inhibited LPS-induced NF-κB activation. Furthermore, our results showed that PLD prevented LPS-induced TLR4 translocation into lipid rafts via disrupting the formation of lipid rafts by inducing cholesterol efflux. In addition, PLD could activate LXRα-ABCA1 signaling pathway which induces cholesterol efflux from cells. The inhibition of TNF-α, IL-6, and IL-1β by PLD could be reversed by SiRNA of LXRα. In conclusion, these results suggested that PLD inhibited LPS-induced inflammatory response by activating LXRα-ABCA1 signaling pathway which disrupted lipid rafts and prevented TLR4 translocation into lipid rafts, thereby inhibiting LPS-induced TLR4 signaling pathway.